Sumoylation is Required for the Cytoplasmic Accumulation of a Subset of mRNAs - Zhang, Hui (Genes (Basel), 2014)
In order to discover novel proteins that promote the nuclear export of newly synthesized mRNAs in mammalian cells, we carried out a limited RNAi screen for proteins required for the proper cytoplasmic distribution of a model intronless mRNA. From this screen we obtained two hits, Ubc9 (SUMO-conjugating E2 enzyme) and GANP (germinal center-associated nuclear protein). Depletion of Ubc9 inhibited the proper cytoplasmic distribution of certain overexpressed intronless mRNAs, while depletion of GANP affected all tested mRNAs. Depletion of Sae1, which is also required for sumoylation, partially inhibited the cytoplasmic distribution of our model mRNA. Interestingly, the block in cytoplasmic accumulation in Ubc9-depleted cells could be overcome if an intron was incorporated into the mRNA. Surprisingly, Ubc9-depleted cells had normal nuclear export of newly synthesized intronless mRNAs, indicating that the observed accumulation of the model mRNA in the nuclei of transfected cells was likely due to some more general perturbation. Indeed, depletion of Ubc9, coupled with the overexpression of the intronless mRNAs, caused the redistribution of the nuclear speckle protein SC35 to cytoplasmic foci. Our results suggest that sumoylation may play a role in the proper assembly of mRNPs and/or the distribution of key RNA binding proteins, and may thus contribute to general protein expression patterns.